Nano low-temperature high-strength ceramic bond and preparation method thereof

By using nano materials and a low-temperature sintering process with a reasonable formula design, nano low-temperature high-strength ceramic binder is prepared, which solves the problem of insufficient strength in low-temperature sintering, realizes high-strength and stable ceramic products, and reduces energy consumption.

CN120717779APending Publication Date: 2025-09-30WEIZE (SUZHOU) NEW MATERIALS TECHNOLOGY CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202511028560.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-25
Publication Date
2025-09-30

AI Technical Summary

Technical Problem

Existing ceramic binders have low strength after low-temperature sintering and cannot meet the needs of modern industry for high strength and low-temperature sintering. Traditional high-temperature sintering consumes energy and affects the dimensional accuracy and performance stability of ceramic products.

Method used

The nano-low-temperature high-strength ceramic binder is prepared by adopting a formula design of components such as nano-silica, nano-alumina, nano-titania, borate glass and phosphate glass, and through a low-temperature sintering process combining ball milling, sintering and molding steps.

Benefits of technology

Achieve high-strength sintering at low temperatures of 800℃-1000℃, reduce energy consumption, improve the strength and stability of ceramic products, and meet the needs of different application scenarios.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a nano low-temperature high-strength ceramic bond and a preparation method thereof. The nano low-temperature high-strength ceramic bond comprises the following raw material components in parts by mass: 20-40 parts of nano silicon dioxide, 15-30 parts of nano aluminum oxide, 5-15 parts of nano titanium oxide, 20-35 parts of borate glass, 10-20 parts of phosphate glass, 3-8 parts of a fluxing agent and 2-5 parts of a sintering aid. The ceramic bond can realize high-strength sintering at a low temperature of 800-1000 DEG C, and compared with a traditional ceramic bond, the sintering temperature is greatly reduced, energy is saved, adverse effects of high temperature on a ceramic product are reduced, and the service life of the ceramic product is prolonged. Through introduction of nano oxides such as nano silicon dioxide, nano aluminum oxide and nano titanium oxide and reasonable formula design, the binding agent has relatively high strength after low-temperature sintering, and the requirements of different application scenes can be met; through the synergistic effect of glass phase components such as borate glass and phosphate glass, the fluxing agent and the sintering aid, the binding agent and the ceramic particles have good adhesive force.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of ceramic materials, in particular to a nanometer low-temperature high-strength ceramic binder and a preparation method thereof. Background Art

[0002] In modern industrial production, ceramic binders are widely used in the fields of abrasive tool manufacturing, refractory materials, etc. With the continuous development of industrial technology, the performance requirements for ceramic binders are getting higher and higher, especially under low-temperature sintering conditions, they need to have high strength, good wear resistance and chemical stability. However, traditional ceramic binders usually need to be sintered at high temperatures of 1200℃-1500℃, which not only consumes a lot of energy and increases production costs, but may also cause deformation of ceramic products, coarse grains and other problems, affecting the dimensional accuracy and performance stability of the products. At the same time, in some temperature-sensitive application scenarios, such as the low-temperature co-firing process of electronic ceramics, low-temperature sintered binders are required. However, the existing low-temperature ceramic binders have low strength after low-temperature sintering and cannot meet actual use requirements, which limits the further expansion of ceramic materials in these fields. Summary of the Invention

[0003] The object of the present invention is to provide a nano low-temperature high-strength ceramic binder and a preparation method thereof, which have the advantage of imparting higher strength to the binder under low-temperature sintering conditions.

[0004] To achieve the above objectives, the present invention provides the following technical solution: a nano-low-temperature, high-strength ceramic binder, whose raw materials include the following components by mass ratio: 20-40 parts of nano-silicon dioxide, 15-30 parts of nano-alumina, 5-15 parts of nano-titanium oxide, 20-35 parts of borate glass, 10-20 parts of phosphate glass, 3-8 parts of flux, and 2-5 parts of sintering aid.

[0005] As a preferred solution, the particle size of the nano-silicon dioxide is in the range of 30 nm to 100 nm, the particle size of the nano-aluminum oxide is in the range of 40 nm to 120 nm, and the particle size of the nano-titanium oxide is in the range of 20 nm to 80 nm.

[0006] As a preferred embodiment, the borate glass is composed of boron oxide and alkali metal oxide, the mass ratio of boron oxide to alkali metal oxide is 7:3, the alkali metal oxide is one or a combination of sodium oxide and potassium oxide, and the phosphate glass is composed of phosphorus pentoxide and metal oxide, the mass ratio of phosphorus pentoxide to metal oxide is 4:1, and the metal oxide is a combination of one or more of calcium oxide, magnesium oxide and barium oxide.

[0007] As a preferred solution, the flux is a combination of one or more of lithium oxide, boron oxide and zinc oxide, and the sintering aid is a combination of one or both of yttrium oxide and cerium oxide.

[0008] A method for preparing a nano-low-temperature high-strength ceramic binder, the method comprising the following steps: S1. Raw material preparation: Weigh nano-silica, nano-alumina, nano-titanium oxide, borate glass, phosphate glass, flux, sintering aid, and other raw materials in a mass ratio of 20-40:15-30:5-15:20-35:10-20:3-8:2-5; S2. Primary ball milling: The weighed raw materials are placed in a ball mill, and zirconium balls and a dispersant are added for ball milling. S3. Primary sintering: The raw material after a ball mill is placed into a high-temperature furnace for sintering; S4 secondary ball milling: The raw material after primary sintering is cooled to room temperature, placed in a ball mill again, a grinding aid is added, and ball milling operation is performed; S5 molding: the raw material after the secondary ball milling is added to the binder, stirred evenly, and then pressed by a press and a mold to form a binder body of the desired shape; S6. Secondary sintering: The formed green body is placed in a low-temperature sintering furnace for sintering; S7. Post-processing: After sintering, the product is cooled to room temperature and then ground and polished to obtain the required dimensional accuracy and surface quality.

[0009] As a preferred solution, in the first ball milling of step S2, the ratio of zirconia balls to raw materials is 3:1-5:1, the dispersant is sodium polyacrylate, the addition amount is 0.5%-1% of the total mass of the raw materials, the ball milling time is 10-15h, and the rotation speed is 200-300r / min.

[0010] As a preferred solution, in the primary sintering of step S3, the sintering temperature is 600°C-800°C, the heating rate is 5°C / min-10°C / min, and the holding time is 2-4h.

[0011] As a preferred solution, in the secondary ball milling of step S4, the grinding aid is ethanol, the addition amount is 5%-10% of the raw material mass, the ball milling time is 5-10 hours, and the rotation speed is 150-250 r / min.

[0012] As a preferred solution, in the molding of step S5, the binder is a polyvinyl alcohol aqueous solution with a concentration of 5%-10%, the pressure of the press is 10-30 MPa, and the holding time is 2-5 minutes.

[0013] As a preferred solution, in the secondary sintering of step S6, the sintering temperature is 800°C-1000°C, the heating rate is 3°C / min-8°C / min, and the holding time is 1-3h.

[0014] Compared with the prior art, the present invention has the following beneficial effects: The ceramic binder of the present invention can achieve high-strength sintering at a low temperature of 800°C-1000°C, which greatly reduces the sintering temperature compared with traditional ceramic binders, saves energy, and reduces the adverse effects of high temperature on ceramic products. By introducing nano-oxides such as nano-silicon dioxide, nano-alumina and nano-titanium oxide and designing a reasonable formula, the binder has higher strength after low-temperature sintering, which can meet the needs of different application scenarios. At the same time, through the synergistic effect of glass phase components such as borate glass and phosphate glass with flux and sintering aids, the binder and ceramic particles have good adhesion, thereby improving the overall performance and stability of ceramic products. DETAILED DESCRIPTION

[0015] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0016] Secondly, the term "one embodiment" or "embodiment" herein refers to a specific feature, structure, or characteristic that may be included in at least one implementation of the present invention. The phrase "in one embodiment" appearing in various places throughout this specification does not necessarily refer to the same embodiment, nor does it refer to a separate or selective embodiment that is mutually exclusive of other embodiments.

[0017] Example 1: A nano-low-temperature high-strength ceramic binder, whose raw materials include the following components by mass ratio: 20-40 parts of nano-silicon dioxide, 15-30 parts of nano-alumina, 5-15 parts of nano-titanium oxide, 20-35 parts of borate glass, 10-20 parts of phosphate glass, 3-8 parts of flux, and 2-5 parts of sintering aid.

[0018] The particle size range of nano-silicon dioxide is 30nm-100nm, the particle size range of nano-aluminum oxide is 40nm-120nm, and the particle size range of nano-titanium oxide is 20nm-80nm.

[0019] Borate glass is composed of boron oxide and alkali metal oxide, the mass ratio of boron oxide to alkali metal oxide is 7:3, and the alkali metal oxide is one or a combination of sodium oxide and potassium oxide. Phosphate glass is composed of phosphorus pentoxide and metal oxide, the mass ratio of phosphorus pentoxide to metal oxide is 4:1, and the metal oxide is a combination of one or more of calcium oxide, magnesium oxide and barium oxide.

[0020] The flux is a combination of one or more of lithium oxide, boron oxide and zinc oxide, and the sintering aid is a combination of one or two of yttrium oxide and cerium oxide.

[0021] A method for preparing a nano-low-temperature high-strength ceramic binder, the preparation method comprising the following steps: S1. Raw material preparation: Weigh nano-silica, nano-alumina, nano-titanium oxide, borate glass, phosphate glass, flux, and sintering aid in a mass ratio of 20:15:5:20:10:3:2. S2. Primary ball milling: The weighed raw materials were placed in a ball mill and zirconium balls and a dispersant were added. The milling process was performed with a 3:1 ratio of zirconium oxide balls to raw materials and sodium polyacrylate as the dispersant at 0.5% of the total weight of the raw materials. The milling time was 10 h at a speed of 200 rpm. S3. Primary sintering: The raw material after a ball mill is placed into a high-temperature furnace and sintered at a sintering temperature of 600°C, a heating rate of 5°C / min, and a holding time of 2h; S4 secondary ball milling: The raw material after a sintering was cooled to room temperature, put into the ball mill again, a grinding aid was added, and the ball milling operation was performed. The grinding aid was ethanol, added in an amount of 5% by mass of the raw material, the milling time was 5h, and the speed was 150r / min; S5 molding: The raw material after the secondary ball milling is added to the binder, stirred evenly, and then pressed by a press and a mold to form a binder body of the desired shape. The binder is a polyvinyl alcohol aqueous solution having a concentration of 5%, a press pressure of 10MPa, and a holding time of 5min. S6. Secondary sintering: The formed green body is placed in a low-temperature sintering furnace for sintering at a temperature of 800°C, a heating rate of 3°C / min, and a holding time of 1h. S7. Post-processing: After sintering, the product is cooled to room temperature and then ground and polished to obtain the required dimensional accuracy and surface quality.

[0022] Example 2, a nano-low-temperature high-strength ceramic binder, whose raw materials include the following components by mass ratio: 20-40 parts of nano-silicon dioxide, 15-30 parts of nano-alumina, 5-15 parts of nano-titanium oxide, 20-35 parts of borate glass, 10-20 parts of phosphate glass, 3-8 parts of flux, and 2-5 parts of sintering aid.

[0023] The particle size range of nano-silicon dioxide is 30nm-100nm, the particle size range of nano-aluminum oxide is 40nm-120nm, and the particle size range of nano-titanium oxide is 20nm-80nm.

[0024] Borate glass is composed of boron oxide and alkali metal oxide, the mass ratio of boron oxide to alkali metal oxide is 7:3, and the alkali metal oxide is one or a combination of sodium oxide and potassium oxide. Phosphate glass is composed of phosphorus pentoxide and metal oxide, the mass ratio of phosphorus pentoxide to metal oxide is 4:1, and the metal oxide is a combination of one or more of calcium oxide, magnesium oxide and barium oxide.

[0025] The flux is a combination of one or more of lithium oxide, boron oxide and zinc oxide, and the sintering aid is a combination of one or two of yttrium oxide and cerium oxide.

[0026] A method for preparing a nano-low-temperature high-strength ceramic binder, the preparation method comprising the following steps: S1. Raw material preparation: Weigh nano-silica, nano-alumina, nano-titanium oxide, borate glass, phosphate glass, flux, and sintering aid in a mass ratio of 30:22:10:27:15:5:3. S2. Primary ball milling: The weighed raw materials were placed in a ball mill and milled with zirconium balls and a dispersant. The ratio of zirconium oxide balls to raw materials was 4:1. The dispersant was sodium polyacrylate, added in an amount of 0.75% of the total raw material weight. The milling time was 12.5 h at a speed of 250 rpm. S3. Primary sintering: The raw material after a ball mill is placed into a high-temperature furnace and sintered at a sintering temperature of 700°C, a heating rate of 7°C / min, and a holding time of 3h; S4 secondary ball milling: The raw material after the primary sintering was cooled to room temperature, placed in a ball mill again, a grinding aid was added, and the ball milling operation was performed. The grinding aid was ethanol, added in an amount of 7% by mass of the raw material, the milling time was 7h, and the speed was 200r / min; S5 molding: The raw material after the secondary ball milling is added to the binder, stirred evenly, and then pressed by a press and a mold to form a binder body of the desired shape. The binder is a polyvinyl alcohol aqueous solution with a concentration of 7.5%. The pressure of the press is 20MPa and the holding time is 3.5min. S6. Secondary sintering: The formed green body is placed in a low-temperature sintering furnace and sintered at a temperature of 900°C, a heating rate of 5°C / min, and a holding time of 2h. S7. Post-processing: After sintering, the product is cooled to room temperature and then ground and polished to obtain the required dimensional accuracy and surface quality.

[0027] Example 3, a nano-low-temperature high-strength ceramic binder, whose raw materials include the following components by mass ratio: 20-40 parts of nano-silicon dioxide, 15-30 parts of nano-alumina, 5-15 parts of nano-titanium oxide, 20-35 parts of borate glass, 10-20 parts of phosphate glass, 3-8 parts of flux, and 2-5 parts of sintering aid.

[0028] The particle size range of nano-silicon dioxide is 30nm-100nm, the particle size range of nano-aluminum oxide is 40nm-120nm, and the particle size range of nano-titanium oxide is 20nm-80nm.

[0029] Borate glass is composed of boron oxide and alkali metal oxide, the mass ratio of boron oxide to alkali metal oxide is 7:3, and the alkali metal oxide is one or a combination of sodium oxide and potassium oxide. Phosphate glass is composed of phosphorus pentoxide and metal oxide, the mass ratio of phosphorus pentoxide to metal oxide is 4:1, and the metal oxide is a combination of one or more of calcium oxide, magnesium oxide and barium oxide.

[0030] The flux is a combination of one or more of lithium oxide, boron oxide and zinc oxide, and the sintering aid is a combination of one or two of yttrium oxide and cerium oxide.

[0031] A method for preparing a nano-low-temperature high-strength ceramic binder, the preparation method comprising the following steps: S1. Raw material preparation: Weigh nano-silica, nano-alumina, nano-titanium oxide, borate glass, phosphate glass, flux, and sintering aid in a mass ratio of 40:30:15:35:20:8:5. S2. Primary ball milling: The weighed raw materials were placed in a ball mill and zirconium balls and a dispersant were added. The milling process was performed with a zirconia ball to raw material ratio of 5:1 and sodium polyacrylate as the dispersant at 1% of the total raw material mass. The milling time was 15 h at a speed of 300 rpm. S3. Primary sintering: The raw material after a ball mill is placed into a high-temperature furnace and sintered at a sintering temperature of 800°C, a heating rate of 10°C / min, and a holding time of 4h; S4 secondary ball milling: The raw material after the primary sintering was cooled to room temperature, placed in a ball mill again, a grinding aid was added, and the ball milling operation was performed. The grinding aid was ethanol, added in an amount of 10% by mass of the raw material, the milling time was 10h, and the speed was 250r / min; S5 molding: The raw material after the secondary ball milling is added to the binder, stirred evenly, and then pressed by a press and a mold to form a binder body of the desired shape. The binder is a polyvinyl alcohol aqueous solution having a concentration of 10%, a press pressure of 30MPa, and a holding time of 2min; S6. Secondary sintering: The formed green body is placed in a low-temperature sintering furnace for sintering at a temperature of 1000°C, a heating rate of 8°C / min, and a holding time of 3h. S7. Post-processing: After sintering, the product is cooled to room temperature and then ground and polished to obtain the required dimensional accuracy and surface quality.

[0032] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the essence and scope of the technical solutions of the present invention.

Claims

1. A nano low-temperature high-strength ceramic binder, characterized in that: The raw materials include the following components by mass ratio: 20-40 parts of nano silicon dioxide, 15-30 parts of nano aluminum oxide, 5-15 parts of nano titanium oxide, 20-35 parts of borate glass, 10-20 parts of phosphate glass, 3-8 parts of flux and 2-5 parts of sintering aid.

2. The nano-low-temperature high-strength ceramic binder according to claim 1, characterized in that: The particle size of the nano-silicon dioxide is in the range of 30nm-100nm, the particle size of the nano-aluminum oxide is in the range of 40nm-120nm, and the particle size of the nano-titanium oxide is in the range of 20nm-80nm.

3. The nano-low temperature high strength ceramic binder according to claim 1, characterized in that: The borate glass is composed of boron oxide and alkali metal oxide, the mass ratio of boron oxide to alkali metal oxide is 7:3, and the alkali metal oxide is one or a combination of sodium oxide and potassium oxide. The phosphate glass is composed of phosphorus pentoxide and metal oxide, the mass ratio of phosphorus pentoxide to metal oxide is 4:1, and the metal oxide is a combination of one or more of calcium oxide, magnesium oxide and barium oxide.

4. The nano-low temperature high strength ceramic binder according to claim 1, characterized in that: The flux is a combination of one or more of lithium oxide, boron oxide and zinc oxide, and the sintering aid is a combination of one or both of yttrium oxide and cerium oxide.

5. A method for preparing the nanometer low-temperature high-strength ceramic binder according to claims 1-4, characterized in that: The preparation method comprises the following steps: S1. Raw material preparation: Weigh nano-silica, nano-alumina, nano-titanium oxide, borate glass, phosphate glass, flux, sintering aid, and other raw materials in a mass ratio of 20-40:15-30:5-15:20-35:10-20:3-8:2-5; S2. Primary ball milling: The weighed raw materials are placed in a ball mill, and zirconium balls and a dispersant are added for ball milling. S3. Primary sintering: The raw material after a ball mill is placed into a high-temperature furnace for sintering; S4 secondary ball milling: The raw material after primary sintering is cooled to room temperature, placed in a ball mill again, a grinding aid is added, and ball milling operation is performed; S5 molding: the raw material after the secondary ball milling is added to the binder, stirred evenly, and then pressed by a press and a mold to form a binder body of the desired shape; S6. Secondary sintering: The formed green body is placed in a low-temperature sintering furnace for sintering; S7. Post-processing: After sintering, the product is cooled to room temperature and then ground and polished to obtain the required dimensional accuracy and surface quality.

6. The method for preparing a nano-low-temperature high-strength ceramic binder according to claim 5, characterized in that: In the first ball milling of step S2, the ratio of zirconium oxide balls to raw materials is 3:1-5:1, the dispersant is sodium polyacrylate, the addition amount is 0.5%-1% of the total mass of the raw materials, the ball milling time is 10-15 hours, and the rotation speed is 200-300 r / min.

7. The method for preparing a nano-low-temperature high-strength ceramic binder according to claim 5, characterized in that: In the primary sintering of step S3, the sintering temperature is 600° C.-800° C., the heating rate is 5° C. / min-10° C. / min, and the holding time is 2-4 hours.

8. The method for preparing a nano-low-temperature high-strength ceramic binder according to claim 5, characterized in that: In the secondary ball milling of step S4, the grinding aid is ethanol, the addition amount is 5%-10% of the mass of the raw material, the ball milling time is 5-10 hours, and the rotation speed is 150-250 r / min.

9. The method for preparing a nano-low-temperature high-strength ceramic binder according to claim 5, characterized in that: In the molding of step S5, the binder is a polyvinyl alcohol aqueous solution with a concentration of 5%-10%, the pressure of the press is 10-30 MPa, and the holding time is 2-5 minutes.

10. The method for preparing a nano-low temperature high strength ceramic binder according to claim 5, characterized in that: In the secondary sintering of step S6, the sintering temperature is 800° C.-1000° C., the heating rate is 3° C. / min-8° C. / min, and the holding time is 1-3 hours.

Citation Information

Patent Citations

  • Carbon-contained nanotube reinforced nano ceramic binding agent diamond grinding wheel and manufacturing method thereof

    CN105252432A

  • Nano ceramic binding agent

    CN107303654A

  • Bonding agent for manufacturing low temperature sintered super hard vitrified abrasive

    CN107971938A

  • Ceramic binding agent and preparation method thereof

    CN108115587A

  • Preparation method of microwave ceramic bond

    CN110614592A